2012
DOI: 10.1002/mrm.24236
|View full text |Cite
|
Sign up to set email alerts
|

Lung ventilation‐ and perfusion‐weighted Fourier decomposition magnetic resonance imaging: In vivo validation with hyperpolarized 3He and dynamic contrast‐enhanced MRI

Abstract: The purpose of this work was to validate ventilation-weighted (VW) and perfusion-weighted (QW) Fourier decomposition (FD) magnetic resonance imaging (MRI) with hyperpolarized (3)He MRI and dynamic contrast-enhanced perfusion (DCE) MRI in a controlled animal experiment. Three healthy pigs were studied on 1.5-T MR scanner. For FD MRI, the VW and QW images were obtained by postprocessing of time-resolved lung image sets. DCE acquisitions were performed immediately after contrast agent injection. (3)He MRI data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 25 publications
3
68
0
2
Order By: Relevance
“…Moreover, recent studies have also demonstrated the reproducibility of FDMRI ventilation-weighted and perfusionweighted images in healthy volunteers (32). Finally FDMRI-to-3 He MRI comparisons in animals showed similar regional abnormalities including pulmonary embolism, atelectasis, and air trapping (30).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, recent studies have also demonstrated the reproducibility of FDMRI ventilation-weighted and perfusionweighted images in healthy volunteers (32). Finally FDMRI-to-3 He MRI comparisons in animals showed similar regional abnormalities including pulmonary embolism, atelectasis, and air trapping (30).…”
Section: Discussionmentioning
confidence: 94%
“…Although rapid (8-15 seconds acquisition time) and well tolerated, inhaled noble gas MRI is dependent on polarized gas and multinuclear magnetic resonance imaging hardware. An alternative approach that exploits Fourier decomposition of free-breathing pulmonary MRI (FDMRI) was first developed by Bauman et al (27) at 1.5 T. This method provides a way to generate quantitative pulmonary maps of ventilation and perfusion using fast pulmonary MRI acquisitions of free-breathing 1 H MRI and nonrigid registration (27)(28)(29)(30)(31)(32)(33). FDMRI was recently compared and validated with single-photon emission computed tomography (SPECT)-CT (28) and 3 He MRI (30) in a porcine model.…”
mentioning
confidence: 99%
“…The technique has been compared to HP 3 He and DCE-MRI in a controlled experiment in pigs. 93 Baseline FD, 3 He and DCE MRI in healthy animals showed homogeneous ventilation and perfusion. Pulmonary embolism was then artificially produced, and FD and DCE MRI perfusion measurements were repeated.…”
Section: Perfusionmentioning
confidence: 95%
“…Nonenhanced techniques (such as arterial spin labeling, in which a control image is subtracted from a radiofrequency pulse-tagged image) can produce perfusion-weighted images, but these methods are technically demanding (163). The use of nonenhanced Fourier decomposition as a method for assessing ventilation and perfusion may be promising, but research into this technique is still in the validation stage (164,165). Newer techniques such as four-dimensional velocity flow mapping may provide additional insights into flow patterns in the pulmonary circulation (166).…”
Section: Mr Imaging and Mr Angiographymentioning
confidence: 98%